Efektivitas Program Bedah Rumah (Study Kasus di Desa Ranoketang Atas Kecamatan Touluaan Kabupaten Minahasa Tenggara) - LIKUAYANG, LIVANDER CORNELIUS; TAMPI, GUSTAAF BUDDY; MAMBO, RULLY (Sam Ratulangi University, 2019)
This House Renovation Program is a very important one to pay attention to,this happens because the government is required to carry out this Home Renovation Program righton target that is in accordance with the requirements that have been determined so that the houserenovation program runs well. The purpose of the House Renovation Program is certainly so thatthe poor can get a decent and comfortable life. The Home Renovation Program needs to payattention to requirements. The purpose of this study is to determine the effectiveness of the HouseRenovation Program in the Village of Ranoketang, Toulagai District, Southeast Minahasa Regency.The benefits of this research are expected to be able to provide a good study to the VillageGovernment in determining or establishing and developing this House Renovation Program and thisresearch might be able to provide information or input to the Toulagai District Government ofMinahasa Regency in general and in particular the Government of Ranoketang Village. Theresearch method used is qualitative research. Data collection techniques used are interviews,observation, and documentation. The Subjects of this Research are the Government of the UpperRanoketang Village and Recipients of the House Renovation Program. Based on the results ofresearch conducted by the House Renovation Program has not been implemented properly wherethe relationship or coordination between the Old Law and BPD is still not good and there is a lot ofmiscommunication between the two parties that makes the House Renovation Program run poorly.For this reason, this study was conducted to answer the question, How is the Effectiveness of theHouse Renovation Program in the Village of Ranoketang, Toul Toul District, Southeast MinahasaRegency. In this study limits through several elements of Effectiveness namely, the Target Approach,Source Approach, Process Approach, and Intergrative Approach.Keywords: Effectiveness,of the House Renovation,Program